Make do and mend. (Imperial War Museums, 2016)
This reminder of the techniques for household economics extolled by the wartime government was published in 1943, as part of the Make do and Mend campaign. It includes tips to spruce up your wardrobe such as remedies for washing silks, mending your clothes and repelling the 'moth menace'.